Determination of lead traces in honey using a fluorimetric method - Talio, María Carolina (2019)
Heavy traces metals may be present in honey being their detection very important for the quality control and it also serves as an indicator of environmental pollution. A new methodology for lead traces determination has been developed based on the quenching effect of the metal on fluorescent emission of 8-hydroxyquinoline and o-phenanthroline at λem = 360 nm (λexc = 250 nm). Experimental variables that influence on fluorimetric sensitivity were optimized by uni-variation assays. The calibration graph using zeroth order regression was linear from 0.105 μg L-1 to 51.8 μg L-1, with correlation coefficient better than 0.998. Under the optimal conditions, the limits of detection and quantification were of 0.035 μg L−1 and 0.105μg L−1, respectively. The trueness of the methodology was assessed trough parallel samples analysis by ICP-MS. The proposed method showed good sensitivity, adequate selectivity with good tolerance to foreign ions, and was applied to the determination of lead trace amounts in honey from San Luis city (Argentina) with satisfactory results.